(3OjhGf GdCMOHs - (3GdGMOH , EHQGgje Hf Ydj GdGMOH GdWQGHdS GdHjQhJj, GdGMOH,J (B1308 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd (B:(3gPg Ledg eeG fXeJg bQjMJi GdaGJQI SCdfi LeYgG CYR GNhGfi(B,(3hCUOb NdGfi,hbO QJHgG Ydi KeGfjI aUhd s
(3BNQgG (B:s
(3ef bUjOI bGdgGJGQjNG cJH Ydi VQjM GdSjO CMeO LdHi hMeOGddg di CQNg hGai aCfi HGdUaG ai GdNdO CMeO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B61s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B488 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B19 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs